Pemeriksaan Hemoglobin untuk Skrinning Dini Anemia pada Siswi MA Raudhatul Jannah Kota Palangka Raya: Hemoglobin Examination for Early Anemia Screening in MA Raudhatul Jannah Female Students, Palangka Raya City - Ramdhani, Fitria Hariati; Hidayani, Al; Ardina, Rinny; Purbayanti, Dwi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Anemia is a condition in which the body lacks red blood cells or has a hemoglobin level of less than 12 g/dL in females and less than 13.5 g/dL in males. Anemia is not only a problem for certain age groups but also affects adolescents who are in the phase of growth. In Indonesia, anemia is particularly common among adolescents. The prevalence of anemia in females is 6% higher than in males. The partner for this project is the female students of MA Raudhatul Jannah in Palangka Raya City. This activity was carried out using two methods: education and hemoglobin testing services. The classification of anemia based on the hemoglobin test results among the female students at MA Raudhatul Jannah in Palangka Raya City, with a total of 54 students, showed that 33 students (61.1%) did not have anemia, 16 students (29.6%) had mild anemia, 4 students (7.4%) had moderate anemia, and 1 student (1.9%) had severe anemia.